2012
DOI: 10.1038/oby.2012.8
|View full text |Cite
|
Sign up to set email alerts
|

Women With and Without Metabolic Disorder Differ in Their Gut Microbiota Composition

Abstract: The aim of this study was to investigate whether overweight/obese women in metabolic disorder group (MDG, n = 27) differ in their gut microbiota composition from overweight/obese women in non‐metabolic disorder group (NMDG, n = 47) and normal weight women group (NWG, n = 11). Gut microbiota was profiled from fecal samples by 16S rRNA fluorescence in situ hybridization and flow cytometry in 85 premenopausal women. Body composition was measured by bioimpedance, and dietary intakes were collected via food diaries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 29 publications
4
57
1
1
Order By: Relevance
“…As such, C leptum (cluster IV) has been associated with both obesity and weight loss (35,36) and was increased in OP and CVOP animals. Further, OTUs only present in OP and their GF recipients were assigned to Clostridium cluster XIVa, which is directly correlated with fat pad mass and BMI (35,37,38) and contains bacterial species known to break down polysaccharides, promoting monosaccharide absorption, enhanced lipogenesis, and lipid storage (4,20). In agreement with this, OP microbiota CV resulted in increase in adipogenic and lipogenic enzyme expression in the liver and adipose tissue as well as increased FA transporters, providing a more efficient transfer and storage of fermented byproducts.…”
Section: T H I S a R T I C L E H A S B E E N E T R A C T E D Rmentioning
confidence: 99%
“…As such, C leptum (cluster IV) has been associated with both obesity and weight loss (35,36) and was increased in OP and CVOP animals. Further, OTUs only present in OP and their GF recipients were assigned to Clostridium cluster XIVa, which is directly correlated with fat pad mass and BMI (35,37,38) and contains bacterial species known to break down polysaccharides, promoting monosaccharide absorption, enhanced lipogenesis, and lipid storage (4,20). In agreement with this, OP microbiota CV resulted in increase in adipogenic and lipogenic enzyme expression in the liver and adipose tissue as well as increased FA transporters, providing a more efficient transfer and storage of fermented byproducts.…”
Section: T H I S a R T I C L E H A S B E E N E T R A C T E D Rmentioning
confidence: 99%
“…Human studies have reported higher fecal concentrations of SCFA in overweight and obese humans compared with their normal-weight counterparts [7e9]. However, the changes in gut microbial composition at phylum and genus/species level that could explain differences between overweight and obese people remain matter of debate [2,7,10].…”
Section: Introductionmentioning
confidence: 98%
“…A negative correlation between Bacteroides and blood pressure, body weight, and fat mass has been reported. 49,50 Therefore, supplementation with bacteria belonging to this genus may improve multiple clinical parameters.…”
Section: Gomez-arango Et Al Blood Pressure and Gut Microbiome Butyratmentioning
confidence: 99%
“…A negative correlation between Bacteroides and blood pressure, body weight, and fat mass has been reported. 49,50 Therefore, supplementation with bacteria belonging to this genus may improve multiple clinical parameters.The gut microbiota can regulate ≈10% of the host's transcriptome, particularly genes involved in immune response, proliferation, and metabolism. 51 Preeclampsia incidence can be reduced by consumption of probiotics in dairy products.…”
mentioning
confidence: 99%